Evaluación de calidad en los servicios de salud: un análisis desde la percepción del usuario - Moreno Treviño, Jorge Omar; Luna Domínguez, Edgar Mauricio; Zurita Garza, Diego René (Horizonte Sanitario, 2021)
We study the determinants of the quality assessment of public and private health services using the Monterrey Metropolitan Area (AMM) as a case study. For this purpose, we used the information from the “Así Vamos 2018” survey, whose design allows representativeness at the state, municipal, and gender levels. We identify which characteristics are most valued in the perception of quality for each type of health service, as well as the context variables of the user that determine this evaluation. Two statistical methods are used: factor analysis and a regression model with limited dependent variable (Tobit). The results suggest significant differences in the determinants of quality between public and private health services. While the most important aspect for IMSS users is the attention of the staff, for Seguro Popular users it is the quality of the facilities. Access to longer office hours and care by medical personnel increases the probability of obtaining better evaluations.